Effect of Different Media on Short Term Storage of Leaping Mullet (Liza saliens (Risso, 1810)) Sperm - Serhat Engin; Muammer Kürşat Fırat; Osman Özden; Cüneyt Suzer; Müge Hekimoğlu; Onurkan Antepli; Şahin Saka (Turkish Journal of Agriculture: Food Science and Technology)
The present study aimed to evaluate the activation characteristics of the leaping mullet spermatozoa and diluted with four different media (D1, D2, D3, D4) for 250 h at 4±2°C. The semen was collected from nine wild fish in Homa Lagoon, İzmir, Turkey in July, during reproductive season. In each trial (n = 9), semen samples were collected and mixed to reduce sperm quality variation to obtain the required gametes for the experiment. The semen was activated with natural seawater (salinity of 34, pH 7.9 and 4±2°C) to determine: motility time, motility rate and viability of sperm. Dilution with inactivation media 1:3 increased motility time of diluted semen than control group. At the end of the experiment, no significant difference was found for the duration of survival in the D2 and D4 groups. The highest survival rate was found in D2 group.